ADUBOS VERDES NA FITORREMEDIAÇÃO DE SOLOS CONTAMINADOS COM O HERBICIDA TEBUTHIURON - Fábio Ribeiro Pires; Sergio de Oliveira Procópio; Caetano Marciano de Souza; José Barbosa dos Santos; Gilson Pereira Silva (Revista Caatinga, 2006)
The tebuthiuron residue, used in the sugar-cane culture, can be found in soil until two or more years after its application. Recent researches are being done using the phytoremediation in the attempt of removing it from the soil. The purpose of this work was to evaluate the effectiveness of the green manure use in the phyitoremediation of the tebuthiuron herbicide. The evaluated species were: Cajanus cajan, Canavalia ensiformis, Dolichos lablab, Pennisetum glaucum, Estizolobium deeringianum, Estizolobium aterrimum and Lupinus albus. These were sown and cultivated in pots containing soil treated with different doses of tebuthiuron (0.0; 0.5; 1.0; and 1.5 kg.ha-1). A control treatment without green manure, submitted to the same dosages, was kept. Sixty days after planting, green manure aerial part of all plants were harvested and soybean was sowed in the same pot, to bioassay accomplishment. Sixty days after sowing, the soybean plants were harvested, being the following evaluations carried out: height of plants, phytotoxicity symptoms and plants above ground dry biomass and leaf area. Until 0.5 kg.ha-1 tebuthiuron dosage, the species that better phytoremediated this herbicide was L. albus. When the soil was treated with tebuthiuron at 1.0 kg.ha-1, the C. ensiformis, followed by L. albus and S. aterrimum, they were the treatments that better phytoremediated tebuthiuron because results in highest plant height, above ground dry biomass and lesser phytotoxicity symptoms and still the biggest foliar area of the soybean plants. When the tebuthiuron was applied at 1.5 kg ha-1 dosage, it was impossible to evaluate the phyitoremediation, as the tested plants were eliminated.